Recent Advance of Liposome Nanoparticles for Nucleic Acid Therapy - Yongguang Gao; Xinhua Liu; Na Chen; Xiaochun Yang; Fang Tang (MDPI AG, 2023)
Gene therapy, as an emerging therapeutic approach, has shown remarkable advantages in the treatment of some major diseases. With the deepening of genomics research, people have gradually realized that the emergence and development of many diseases are related to genetic abnormalities. Therefore, nucleic acid drugs are gradually becoming a new boon in the treatment of diseases (especially tumors and genetic diseases). It is conservatively estimated that the global market of nucleic acid drugs will exceed $20 billion by 2025. They are simple in design, mature in synthesis, and have good biocompatibility. However, the shortcomings of nucleic acid, such as poor stability, low bioavailability, and poor targeting, greatly limit the clinical application of nucleic acid. Liposome nanoparticles can wrap nucleic acid drugs in internal cavities, increase the stability of nucleic acid and prolong blood circulation time, thus improving the transfection efficiency. This review focuses on the recent advances and potential applications of liposome nanoparticles modified with nucleic acid drugs (DNA, RNA, and ASO) and different chemical molecules (peptides, polymers, dendrimers, fluorescent molecules, magnetic nanoparticles, and receptor targeting molecules). The ability of liposome nanoparticles to deliver nucleic acid drugs is also discussed in detail. We hope that this review will help researchers design safer and more efficient liposome nanoparticles, and accelerate the application of nucleic acid drugs in gene therapy.